Sinking of INS Khukri : survivors' stories - Cardozo, Ian. (New Delhi Lotus|Rolli Books, 2015)
9 December 1971. 8.45 p.m. Torpedoed by a Pakistani submarine, the INS Khukri sank within minutes. Along with the ship, 178 sailors and 18 officers made the supreme sacrifice. Last seen calmly puffing on his cigarette, Captain Mahendra Nath Mulla, captain of the Khukri, chose to go down with his ship. This defining moment of the 1971 war between India and Pakistan is the basis of Major General Ian Cardozo's attempt to understand what happened that day and why. Major General Cardozo brings fresh insight into the hellish ordeal by including the heartfelt accounts of the survivors and of the members of their families. These accounts transform the stereotypical understanding of the incident; they also supplement it. We glimpse fear, trauma and death at first hand. In the annals of war writing, General Cardozo humanizes this cataclysmic event as never before.
What happened in 1971.
Keywords: Khukri (Ship)